2004
DOI: 10.1097/01.aog.0000123269.86525.c4
|View full text |Cite
|
Sign up to set email alerts
|

Paracervical Block in Incomplete Abortion Using Manual Vacuum Aspiration: Randomized Clinical Trial

Abstract: The paracervical block technique used in this study along with psychological support was comparable with pain control using psychological support alone; neither pain management regimen provided sufficient pain control. It is recommended that randomized comparative studies be designed to determine the effectiveness of other paracervical block techniques and the efficacy of the use of analgesics in patients suffering from incomplete abortion treated with manual vacuum aspiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…MVA group appreciated less pain and required less analgesia in comparison with EVA group, which was similar to Gomez et al [8] study who found significant differences when comparing level of pre-operative and intraoperative pain (p<0.001). Das Vinita et al 2 and Goldberg et al 5 had relatively more complications in MVA group as 9% and 2% as compared to 6% and 2% in EVA group respectively.…”
Section: Discussionsupporting
confidence: 88%
“…MVA group appreciated less pain and required less analgesia in comparison with EVA group, which was similar to Gomez et al [8] study who found significant differences when comparing level of pre-operative and intraoperative pain (p<0.001). Das Vinita et al 2 and Goldberg et al 5 had relatively more complications in MVA group as 9% and 2% as compared to 6% and 2% in EVA group respectively.…”
Section: Discussionsupporting
confidence: 88%
“…Pain control is one of the most relevant issues in managing incomplete abortion. In one study that evaluated postoperative pain using paracervical block or no analgesics, there was no difference between using paracervical block and using no medication for pain management [8]. In that study, the incidence of adverse effects was more commonly seen in the groups using meperidine than in the groups using diclofenac and paracervical block.…”
Section: Discussionmentioning
confidence: 93%
“…First trimester uterine bleeding due to incomplete abortion continues to be one of the main causes of maternal morbidity and mortality in developing countries. Ongoing studies are seeking the optimal approach to address this issue [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significance of the separate innervation of the fundus as a key to understanding the insufficient pain relief during intracavitary surgery under PCB is underpinned by results obtained during hysteroscopic sterilization under a paracervical block (which provided effective pain relief for cervical manipulations but did not reduce the pain associated with upper uterine/tubal manipulation when placing the devices) [10] as well as during vacuum aspiration under PCB after incomplete miscarriage [11]. These results are in line with conclusions in the latest Cochrane review on PCB for uterine interventions [12].…”
Section: Discussionmentioning
confidence: 99%